EFEKTIVITAS MODEL RECIPROCAL TEACHING DENGAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION DALAM PEMBELAJARAN PUISI - Hidayat Hidayat; Agus Hamdani; Deasy Aditya Damayanti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This research is entitled "Effectiveness of the Reciprocal Teaching Model with the STAD Model in Learning Poetry for Class X SMA Negeri 11 Garut in the Academic Year 2022/2023". theoretical. This study aims to analyze differences in the effectiveness of learning by using the Student Team Achievement Division (STAD) and Reciprocal Teaching models in improving poetry learning in class X students of SMA Negeri 11 Garut. This study used a quasi-experimental method, namely by giving treatment to two different sample classes. The research population was students of class X MIPA SMA Negeri 11 Garut with a sample of class X MIPA 7 as the Student Team Achievement Division (STAD) class and class X MIPA 8 as the Reciprocal Teaching class. Data collection techniques in the form of tests carried out after being given treatment. The results showed that (1) an increase in students' poetry learning abilities using the Student Team Achievement Division (STAD) model obtained a high increase. (2) Increasing students' poetry learning ability using the Reciprocal Teaching model experienced a high increase. (3) Learning with the Reciprocal Teaching model is more effective than learning with the Student Team Achievement Division (STAD) model in improving students' poetry learning abilities. Based on the research findings above, the two learning models are appropriate for use by teachers as an alternative to improve poetry learning abilities.Keywords: Poetry Learning, STAD, Reciprocal Teaching.